2021
DOI: 10.1088/1361-6595/abe4e2
|View full text |Cite
|
Sign up to set email alerts
|

Remote streamer initiation on dielectric surface

Abstract: We study the origin of filamentary patterns in a sinusoidally driven surface barrier discharge at high over-voltage in atmospheric pressure air. Using a time-correlated single-photon counting based optical emission spectroscopy, we reveal ultrafast processes within generated discharges in both polarities of the applied voltage. For negative polarity, we observe initiation of complex streamer cascade which emerges far from the bare cathode. This event is responsible for long filamentary structure detected by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 86 publications
(174 reference statements)
1
13
0
Order By: Relevance
“…A similar phenomenon, namely the formation of a bidirectional ionization wave, was observed in the recently published work [49], which presents the dynamics of ionization waves in a sinusoidally driven HV (15.43 kHz, 25 kV pp peakto-peak) surface barrier discharge in atmospheric-pressure air. The authors observed, using sub-nanosecond-resolved optical emission spectroscopy based on the time-correlated singlephoton counting technique, a remote streamer initiation on dielectric surface.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…A similar phenomenon, namely the formation of a bidirectional ionization wave, was observed in the recently published work [49], which presents the dynamics of ionization waves in a sinusoidally driven HV (15.43 kHz, 25 kV pp peakto-peak) surface barrier discharge in atmospheric-pressure air. The authors observed, using sub-nanosecond-resolved optical emission spectroscopy based on the time-correlated singlephoton counting technique, a remote streamer initiation on dielectric surface.…”
Section: Discussionsupporting
confidence: 76%
“…An important distinguishing feature of [49] compared to the present work is that it was carried out in a repetitively pulsed SDBD, where an important role should be played by the charge remaining on the dielectric after previous pulses (see review [12]). This complicates the analysis of the results [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A different experimental approach for determining the reduced electric field from the intensity ratio method is by using photo multipliers instead of an ICCD. Time correlated single photon counting [10,42,43] has the advantage of a much improved temporal resolution, going down to tens of picoseconds, compared to the hundredths of picoseconds generally attained by an ICCD, this matters especially for the time derivatives in the ratio calculation. However, interpretation-wise, the ICCD provides directly correlated spatial and spectral dimensions to the measurement, allowing the spectral fitting of the captured data and spatial verification of the 2D single-shot imaging.…”
Section: Figurementioning
confidence: 99%